A conceptual model for evaluation of synergies in mergers and acquisitions: A critical review of the literature - G. V.M. Kode; J. C. Ford; M. M. Sutherland (South African Journal of Business Management, 2003)
The vast majority of mergers and acquisitions rely on synergies in the value creation process. Only a small proportion of mergers and acquisitions are undertaken for non-synergistic reasons. Many mergers and acquisitions never achieve the pre-deal successes that are used to motivate and justify the payment of huge premiums over the stand-alone value of the target companies. Because synergies are used to justify the payment of premiums, executive management, need to fully understand how to evaluate synergies.This model building exercise has enabled the development of an integrated model for the evaluation of synergies that uses the best practices identified from the writings of the authors under review. The model, therefore, provides academics and executive management with a framework for better understanding synergies and some techniques to ensure the realisation of productive synergies in the implementation of mergers and acquisitions.
Keywords: 650